Neonatal lymphatic flow disorders: central lymphatic flow disorder and isolated chylothorax, diagnosis and treatment using novel lymphatic imaging and interventions technique. Issue 2 (31st January 2022) - Rabinowitz, Deborah; Dysart, Kevin; Itkin, Maxim
Abstract : Purpose of review: Neonatal lymphatic disorders (NLDs) are conditions that are relatively rare and difficult to treat. The recent development of lymphatic imaging, such as Dynamic Contrast-Enhanced MR Lymphangiography and Intranodal Lymphangiography has led to a new, better understanding of the anatomical substrate and pathophysiological mechanisms of the diseases. Consequently, this has allowed the development of new targeted therapeutic interventions as well as prognostication for this population with lymphatic flow disorders. Recent findings: The underlying causes of all NLD is an obstruction or altered flow of the central lymphatic flow. Two types of NLD have been described: isolated neonatal chylothorax and central lymphatic flow disorder (CLFD). Isolated neonatal chylothorax can be treated successfully with oil-based contrast (lipiodol) embolization. CLFD secondary to obstruction of the thoraco-venous junction can be successfully treated with surgical thoracic duct-venous anastomosis. CLFD caused by elevated central pressure and/or thoracic duct dysplasia can be treated medically, including with new systemic therapies such as mammalian target of rapamycin inhibitors. Summary: New diagnostic and interventional tools have recently allowed for classification, prognostication, and targeted interventions for neonatal patients with lymphatic flow disorders. Further research will build on these discoveries.